2019
DOI: 10.3390/antiox8090345
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Chemical Compositions, Antioxidant, and Anti-Photoaging Activities of Paeonia suffruticosa Flowers at Different Flowering Stages

Abstract: Paeonia suffruticosa is an ornamental, edible, and medicinal plant. The ethanolic extracts of P. suffruticosa bud and flower were examined for their antioxidant, anti-photoaging, and phytochemical properties prior to chemometric analysis. The results showed that the bud ethanolic extract (BEE) and the flower (the early flowering stage) ethanolic extract (FEE) had better antioxidant activities, and significantly increased the activities of superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) and reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 40 publications
1
17
0
1
Order By: Relevance
“…In a recent study, it was found that paeoniflorin can reduce the response injury of astrocytes and microglia by inhibiting the phosphorylation of apoptotic signal‐regulating kinase 1 (ASK1), inhibiting its neuroinflammatory effect and treating chronic neuropathic pain in rats . It is worth noting that paeoniflorin also has pharmacological activities such as hypoglycaemic and lipid‐lowering, antioxidant and antiphotoaging …”
Section: Other Related Bioactivities Of Paeoniflorinmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, it was found that paeoniflorin can reduce the response injury of astrocytes and microglia by inhibiting the phosphorylation of apoptotic signal‐regulating kinase 1 (ASK1), inhibiting its neuroinflammatory effect and treating chronic neuropathic pain in rats . It is worth noting that paeoniflorin also has pharmacological activities such as hypoglycaemic and lipid‐lowering, antioxidant and antiphotoaging …”
Section: Other Related Bioactivities Of Paeoniflorinmentioning
confidence: 99%
“…[92] It is worth noting that paeoniflorin also has pharmacological activities such as hypoglycaemic and lipid-lowering, antioxidant and antiphotoaging. [93,94] [84] 0.01, 0.1, 0.5, 1.0, 2.0 mg/ml…”
Section: Human Cervical Carcinoma Cell Line Lelamentioning
confidence: 99%
“…The product ion at m/z 283.0357 was produced via the loss of the monoterpene (C 10 H 12 O 4 ) core of the precursor ions. Based on the secondary fragmentation data and mass spectral fragmentation behaviour, compound 1 was identified as paeoniflorin 14,15 . The fragmentation pathway of paeoniflorin in the negative ion mode is illustrated in Figures 3 and 4.…”
Section: Resultsmentioning
confidence: 99%
“…As a rule, TAs are considered non-toxic in small doses [ 13 , 14 ] and exhibit antitumor effects [ 15 ]. The presence of TA in natural components can reduce tumor necrosis factor levels [ 16 ] and weaken the inflammatory cytokine expression [ 17 ]. Previously, it was shown that TA crosslinked into a compacting collagen gel predominantly inhibited proliferation of high-melanoma A375 cells with metastatic potential [ 18 ].…”
Section: Introductionmentioning
confidence: 99%